2020
DOI: 10.1016/j.jff.2020.103945
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights in health-promoting properties of sweet cherries

Abstract: Sweet cherry (Prunus avium L.) is one of the most popular and appreciated temperate fruit not only for its sensory and nutritional properties, but also for its content in bioactive compounds. Consumption of sweet cherries brings beneficial effects on to health, which include prevention and modulatory effects in several chronic diseases such as (diabetes mellitus, cancer, cardiovascular and other inflammatory diseases). The presence of natural polyphenolic compounds with high antioxidant potential might drive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 94 publications
1
50
0
4
Order By: Relevance
“…Among the berries, the antioxidative effects of blueberry [ 63 , 64 , 65 ], chokeberry [ 66 , 67 , 68 , 69 ], cranberry [ 69 , 70 , 71 ], and goji berry [ 72 , 73 ] in reducing the risk of osteoporosis were reported. In recent years, new evidence has emerged of the health-promoting effects of sweat cherries on bone impairment associated with childhood obesity [ 74 , 75 ] demonstrated that obese children and adolescents bone impairment is sustained by spontaneous osteoclastogenesis, which can be limited in vitro by polyphenols presence. Research conducted on cultured peripheral blood mononuclear cells (PBMCs) from obese children showed that sweet cherry extract reduced the spontaneous formation of multinucleated osteoclasts in examined cells.…”
Section: Bone and Osteoporosismentioning
confidence: 99%
“…Among the berries, the antioxidative effects of blueberry [ 63 , 64 , 65 ], chokeberry [ 66 , 67 , 68 , 69 ], cranberry [ 69 , 70 , 71 ], and goji berry [ 72 , 73 ] in reducing the risk of osteoporosis were reported. In recent years, new evidence has emerged of the health-promoting effects of sweat cherries on bone impairment associated with childhood obesity [ 74 , 75 ] demonstrated that obese children and adolescents bone impairment is sustained by spontaneous osteoclastogenesis, which can be limited in vitro by polyphenols presence. Research conducted on cultured peripheral blood mononuclear cells (PBMCs) from obese children showed that sweet cherry extract reduced the spontaneous formation of multinucleated osteoclasts in examined cells.…”
Section: Bone and Osteoporosismentioning
confidence: 99%
“…Also important is the chemical composition of sweet cherries which has a great influence on the sensory quality of the fruits [ 28 ]. These fruits are a source of bioactive compounds, such as, natural polyphenolic compounds, that enhance health benefits (health promoters), revealing an anti-cancer, anti-inflammatory, and antioxidant power, among others [ 3 , 29 , 30 , 31 , 32 ]. Therefore, it is important to evaluate their impact on consumer acceptance, trying to achieve the optimal combination of taste and health-promoting compounds [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most well-documented biological effects of sweet cherry extract encompass its antioxidant and anti-inflammatory properties [ 8 , 11 , 12 ]. The continuous increase of oxidative stress (OS) and chronic inflammation are important driving forces in the carcinogenic process, promoting cancer onset, progression and aggressiveness [ 13 , 14 , 15 , 16 ], which per se justifies envisaging the anti-cancer role of sweet cherry.…”
Section: Introductionmentioning
confidence: 99%